UJI EFEKTIVITAS ANTIBAKTERI INFUSA DAUN SIRSAK TUA (Annona muricata L.) TERHADAP Propionibacterium acnes - Fitriyanti; Ari Surya Pratama; Karunita Ika Astuti (Politeknik Medica Farma Husada Mataram, 2019)
Acne is a skin disease. One of the common bacteria that infects acne is Propionibacterium acnes. Natural ingredient that can be used to treat acne is Annona muricata L. leaves. This study aims to determine the compound content and effective concentration of antibacterial infusion of old Annona muricata L leaves against p.acnes bacteria. This research is experimental by using the liquid dilution method, solid dilution method, and the diffusion well method. The extraction method used in this study is an infusion. Infusion test solution using concentrations of 1.56%; 3.12%; 6.25%; 12.5%; 25%; 50%; 100%; and 200%. The results of this study are old Annona muricata L leaves infusion containing flavonoid compounds, saponins, and tannins. The results of the dilution test obtained the MIC value at a concentration of 25% and the MBC value was found at a concentration of 100%. In the dilution test the infusion of old Annona muricata L leaves infusion with concentrations of 100% and 200% has strong antibacterial activity and effective concentrations or MEC infusion and old Annona muricata L are found at concentrations of 100% with an average inhibition zone diameter of 11 mm (strong category).